2018
DOI: 10.1073/pnas.1718363115
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional mutagenesis mediated by 8-oxoG induces translational errors in mammalian cells

Abstract: Reactive oxygen species formed within the mammalian cell can produce 8-oxo-7,8-dihydroguanine (8-oxoG) in mRNA, which can cause base mispairing during gene expression. Here we found that administration of 8-oxoGTP in MTH1-knockdown cells results in increased 8-oxoG content in mRNA. Under this condition, an amber mutation of the reporter luciferase is suppressed. Using second-generation sequencing techniques, we found that U-to-G changes at preassigned sites of the luciferase transcript increased when 8-oxoGTP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 28 publications
2
49
0
Order By: Relevance
“…Indeed, Nunomura et al (10) demonstrated that RNA oxidation is a prominent feature of neuronal vulnerability in patients with Alzheimer's disease. More recently, we showed that there is the casual relationship between RNA oxidation and Aβ peptide formation using CHO cells to which 8-oxoGTP is externally supplied (11). Cells carrying 8-oxoG in messenger RNA secreted 28 types of previously unknown Aβ-derived peptides, in addition to a greater amount of pathogenic Aβ peptides that have thus far been characterized.…”
mentioning
confidence: 99%
“…Indeed, Nunomura et al (10) demonstrated that RNA oxidation is a prominent feature of neuronal vulnerability in patients with Alzheimer's disease. More recently, we showed that there is the casual relationship between RNA oxidation and Aβ peptide formation using CHO cells to which 8-oxoGTP is externally supplied (11). Cells carrying 8-oxoG in messenger RNA secreted 28 types of previously unknown Aβ-derived peptides, in addition to a greater amount of pathogenic Aβ peptides that have thus far been characterized.…”
mentioning
confidence: 99%
“…Lastly, another point of relevance relates to the biological impact that oxidative stress has on RNA. Oxidized RNA has been shown to be present in various types of RNA, including rRNA, mRNA, or miRNA, and this also makes riboswitches prone to oxidative damage. Although this relationship has not been established, it is plausible that such processes might play a role in dysfunction or altered regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…RNA sequencing of ASDCASK_SS neurons indicated that the mutated T/U is modified to the reference G nucleotide, suggesting that RNA editing is involved in the rescue mechanism. While reports on U-to-G RNA editing are rare, these mechanisms are shown to be relevant for synaptic transcripts and may be involved in the rescue of CASKWT in the ASDCASK_SS (Dai et al, 2018;Reid et al, 2008).…”
Section: Cask-related Disorders Have Emerged As An Important Genetic mentioning
confidence: 99%
“…We have earlier studied pre-and perinatal environmental exposures in the RATSS twin sample, including the ASDCASK_SS case and his co-twin, and showed that uptake of essential metals zinc and manganese, and the neurotoxic metal lead were associated with variable manifestation of autistic traits and ASD diagnoses (Arora et al, 2017). These environmental stressors could potentially affect the RNA processing efficiency and mediate gene-environment interactions leading to differences in outcomes of the twin pair (Dai et al, 2018;Dick et al, 2019;Shomron et al, 2002).…”
Section: Cask-related Disorders Have Emerged As An Important Genetic mentioning
confidence: 99%